Investigating the Use of Webtoon Application for Learning English Skills - Salsabila Fauziah; Nasrullah Nasrullah (Universitas Muhammadiyah Barru, 2023)
There are many language skills that must be mastered in learning English, consequently the proper media is required to accommodate this need. Webtoon is the solution for these problems, which is a very popular digital comic application with more than 100 million downloads and provides a wide variety of genres which can help to learn English skills. The previous research examined the use of webtoon as a learning media to mastering vocabulary, improve students reading skills, speaking skills and writing skills. However, no research has been conducted on the use of webtoon for all English language skills. Therefore, this study aims to investigate of using webtoon applications for students’ English skills. This study employed qualitative approach, and the design used in this study was systematic literature review. The method of collecting data in this research is by using 25 research articles that were collected from Google Scholar, ResearchGate, Microsoft Academic, ScienceDirect, and the Perpustakaan Nasional. From twenty five articles that researchers have been investigated it was found that webtoon media has a big impact on students’ English skills. The illustration images available on the webtoon also help in understanding the story and difficult words for the readers and also do not make the students bored. Therefore, this article is structured to investigate how the use of webtoon for students could increase their English skills.